PERANAN TRICHODERMA DALAM MENDUKUNG PERTANIAN ORGANIK DI DESA TANAK KAKEN KECAMATAN SAKRA BARAT KABUPATEN LOMBOK TIMUR: The Function Of Trichoderma In Supporting Organic Agriculture In Tanak Kaken Village, Sakra Barat District, East Lombok Regency - Apzani, Wawan; Haryantini, Baiq Azizah; Sunantra, I Made; Wardhana, Agung Widya; Arifin, Zainal; Baharuddin, Baharuddin; Zainab, Siti (Al-Amal: Jurnal Pengabdian Masyarakat, 2023)
Organic plants are plants produced without adding synthetic materials or genetic engineering but only using natural ingredients. Where currently the need for organic vegetables and fruit is increasing along with the improvement in people's quality of life. However, the increase in demand is not commensurate with its availability on the market. This activity is carried out in order to increase the supply of quality organic food that the community needs by utilizing unused organic materials such as livestock waste that is thrown away in vain. This activity uses a material presentation method and is followed by a direct demonstration of making bioactivator powder organic fertilizer fermented by Trichoderma spp. The result of this activity is an organic fertilizer with Trichoderma spp.coffee leaf bioactivator powder which can increase soil fertility and plant growth and reduce the proliferation of pests and diseases so that organic farming in Tanak Kaken village can be achieved